Pendidikan yang Membebaskan: Sebuah Reinterpretasi Filsafat Pendidikan Paulo Freire - Reni, Siti; Asbari, Masduki; Ramadhan, Mohamad Biazt (Journal of Information Systems and Management (JISMA), 2024)
This article is a review which is a critical reading of a guidebook that inspires and provides motivation for readers entitled "Liberating Education: A Reinterpretation of Paulo Freire's Educational Philosophy" by Akhmad Muhaimin Azzet, which is an attempt to re-actualize the concept of liberating education in the educational context in Indonesia. This book discusses the concept of liberating education from the perspective of Paulo Freire, a Brazilian education expert who is famous for this concept. This book is divided into three parts. The first part discusses Paulo Freire's educational philosophy. The second part discusses the concept of liberating education in the context of education in Indonesia. The third part discusses the challenges and opportunities of liberating education in Indonesia. In this book, Akhmad Muhaimin Azzet states that liberating education is education that aims to liberate humans from various forms of oppression, whether physical, mental or spiritual oppression. Liberating education also aims to build independent, critical and responsible humans. This book makes a significant contribution to the development of education in Indonesia. This book offers a new perspective on liberating education, which can become the basis for the development of more democratic and egalitarian education in Indonesia.